Antecedents towards social circular consumption of food wastes in emerging economies: Transition towards food circular economy. Issue 4 (15th March 2022) - Kumari, Sneha; Bharti, Nisha; Rahaman, Saidur
Abstract: Food waste not only challenges food security but also contributes to carbon gas emissions leading to climate change. Hence, food wastes management evolved as an important measure for sustainability and circular economy. Time and again, food waste management has serious concerns for the population. Despite the growing concept of circular economy in food waste management, there is a need to understand the antecedents which lead to reuse, recycling, and reducing food wastes. The study aims to address the following research question: What are the antecedents for circular consumption of food wastes and how can we prioritize those risks at the bottom of the pyramid? The study aims to understand all the antecedents identified using the Delphi technique and an extensive literature review. The antecedents have been further analyzed and prioritized using the DEMATEL technique. The prime respondents of the study are practitioners, distributors, households, and waste pickers. The study has derived 15 antecedents of food waste management and validated them through experts. The final selected antecedents have been analyzed and prioritized using DEMATEL. The study proposes a new model for circular consumption of food using Delphi and DEMATEL methodology. The antecedents have been further linked to strategizing business for the same. The outcome will help the practitioners to take appropriate actions for managing food waste. The study will add to the managerial and policy recommendations for managing food waste.